Does Brand Awareness Mediate the Effect of Social Media Marketing on Purchase Intention? - PUTRA, I Komang Mahayana; GEDE, I Gusti Ketut; WIRGA, I Wayan; SANJAYA, Ida Bagus; YASA, I Ketut (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose: This research examines the role of brand awareness in mediating the effect of social media marketing on purchase intention for MS Glow Men products. MS Glow Men is a skincare brand specifically for men and men made from natural ingredients, which is quite well known among men's skincare product users. Botanicals conducted this research in Denpasar City. Methodology: Research data was collected using an online questionnaire with a sample size of 100 respondents. The sample determination method uses a non-probability sampling method, namely purposive sampling. This research uses path analysis techniques. Findings: The research results show that social media marketing has a positive and significant effect on purchase intention; social media marketing has a positive and significant effect on brand awareness; brand awareness has a positive and significant effect on purchase intention; and brand awareness mediates the effect of social media marketing on purchase intention. Implication: The MS Glow Men company should increase interactive content on social media, create exciting campaigns, and focus more on introducing the advantages of its products compared to competitors.